POLITICAL CLIQUES AND THE FORMATION OF POLITICAL PARTY COALITIONS: A Study Of The “Banten Maju” Coalition In The 2024 Banten Gubernatorial Election - Immanuel, Glenn Kevin; Muradi, Muradi; Paskarina, Caroline (Department of Government, FISIP, Universitas Padjadjaran, 2025)
This study analyzes how the practice of political cliques influences the formation process of the Banten Maju Coalition in the context of the 2024 Banten gubernatorial election. The researcher employs the concept of political cliques and utilizes a qualitative research method, with primary data supported by secondary data through a literature review to analyze the role of political cliques in the coalition’s formation. The study finds that the formation of the Banten Maju Coalition in the 2024 gubernatorial election is not based on ideological similarity or shared political platforms among the participating political parties. Instead, the coalition is predominantly influenced by pragmatic interests rooted in the power of political cliques at the national level. Key figures within the coalition parties hold significant influence in determining the coalition’s direction, with most decisions made by the parties’ central executive boards (DPP).